The Creator - Edwards, Gareth, 1975-; Weitz, Chris, 1969-; Washington, John David, 1984-; Chan, Gemma, 1982-; Watanabe, Ken, 1959-; Zimmer, Hans; Regency Enterprises; E1 Entertainment (Firm); New Regency (Firm); Bad Dreams (Firm); 20th Century Studios ([Los Angeles, CA] : 20th Century Studios, 2023)
Amidst a future war between the human race and the forces of artificial intelligence, Joshua, a hardened ex-special forces agent grieving the disappearance of his wife, is recruited to hunt down and kill the Creator, the elusive architect of advanced AI who has developed a mysterious weapon with the power to end the war and mankind itself. Joshua and his team of elite operatives journey across enemy lines, into the dark heart of AI-occupied territory only to discover the world-ending weapon he's been instructed to destroy is an AI in the form of a young child.
Originally released as a motion picture in 2023.
Wide screen (2.76:1).
new dvd 2024 summer.
Director of photography, Greig Fraser, Oren Soffer ; editors, Hank Corwin, Joe Walker, Scott Morris ; music by Hans Zimmer.
John David Washington, Gemma Chan, Ken Watanbe, Sturgill Simpson, Amar Chadha-Patel, Ralph Ineson, Veronica Ngo, Marc Menchaca, Madeleine Yuna Voyles, Allison Janney.
MPAA rating: PG-13; for violence, some bloody images and strong language.
Keywords: Artificial intelligence -- Drama; Humanity -- Drama; Imaginary wars and battles -- Drama; Imaginary wars and battles; Action and adventure films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Thriller films; Feature films; Science fiction films